A Theoretical Investigation of Transport Layer‐Free Homojunction Perovskite Solar Cells via a Detailed Photoelectric Simulation. Issue 12 (15th January 2023) - Zhang, Yuqi; Yang, Zhenhai; Ma, Tianshu; Ai, Zhenhai; Wang, Changlei; Li, Xiaofeng
Abstract: Although the conventional n‐i‐p or p‐i‐n perovskite solar cells (PSCs) can produce ultrahigh efficiency (>25%), complex synthesis/deposition processes together with strict requirements for preparing the hole‐ and electron‐transport layers (HTLs and ETLs) pose a challenge to accessing low‐cost perovskite devices. To address this issue, a simple strategy of employing a self‐doped perovskite homojunction to replace the HTLs and ETLs has been widely proposed. However, this type of TL‐free homojunction PSCs is usually endowed with poor efficiency. Here, the design principles and working mechanisms of the TL‐free homojunction PSCs are clarified via a rigorous photoelectric simulation. The potential of this type of device is unlocked by optimizing the structural/electrical parameters including thickness, doping concentration, bulk/interface defect concentration, contact barrier, and mobility of n‐perovskite and p‐perovskite. To further uncover the intrinsic physical behavior, ion migration, and photon recycling effects on this type of TL‐free homojunction PSCs are also studied. In addition, devices with different types of structures including TL‐free inverted, ETL‐free, and HTL‐free designs are briefly discussed. Finally, a clear roadmap for the promotion of device efficiency is proposed, providing valuable guidance for designing high‐efficient TL‐free homojunction PSCs. Abstract : A rigorous photo‐electric simulation is conducted for transport layer‐free homojunction perovskite solar cells to clarify their design principles and working mechanisms by investigating a series of structural/electrical parameters of n‐perovskite and p‐perovskite, and uncover the underlying physical behavior by addressing the ion migration and photon recycling effects. A clear route map for the promotion of device efficiency is proposed.